PENYULUHAN PENTINGNYA AKTIVITAS FISIK DALAM PENCEGAHAN OBESITAS DAN SKRINING STATUS GIZI DI PEJAGALAN JAKARTA BARAT - Lontoh, Susy Olivia; Jap, Aydhing Nathasya; Haryanto, Yonathan Julian (Jurnal Serina Abdimas, 2023)
Low levels of physical activity and obesity in young adults are major challenges in public health in Indonesia. Lack of movement and laziness to exercise make residents around Pejagalan become inactive and have problems with weight. The community service team conducted activities to measure nutritional status, physical activity levels and health education related to physical activity in an effort to prevent obesity in young adults at Pejagalan, West Jakarta. The purpose of this activity is screening for nutritional status, level of physical activity and education related to physical activity to prevent overweight in young adults at Pejagalan, West Jakarta. Community service activities are carried out on Thursday, May 10, 2023 at 13.00-16.00 at Pejagalan, West Jakarta. Target target activities are young adults aged 20-65 years. Nutritional status is calculated based on the ratio between body weight (BB) in kg and the square of height (TB) in meters. Participants were given a questionnaire related to physical activity in Godin Shepard's spare time to get an overview of the participants' physical activity levels. The activity was attended by 30 participants with an age range of 20-60 years, consisting of 16 male participants and 14 female participants. Participants' weight ranged from 47-93 kg and height 148-183 cm. The level of physical activity of the counseling participants was 20 participants with a low level of physical activity and 5 participants with a high level of activity. There were 20 (66.7%) and 10 (33.3%) participants who rarely exercised in 1 week and exercised regularly. Participants whose nutritional status was obese were 10 (33.3%) participants and 6 (20%) participants including overweight nutritional status. ABSTRAK Tingkat aktivitas fisik yang rendah dan obesitas pada dewasa muda menjadi tantangan utama di bidang kesehatan masyarakat di Indonesia. Kurang gerak serta malas berolahraga membuat warga sekitar Pejagalan menjadi tidak aktif dan bermasalah dengan berat badan.Tim pengabdian masyarakat melakukan kegiatan pengukuran status gizi, tingkat aktivitas fisik serta edukasi kesehatan terkait aktivitas fisik dalam upaya pencegahan obesitas pada dewasa muda di Pejagalan Jakarta Barat. Tujuan kegiatan ini adalah skrining status gizi, tingkat aktivitas fisik dan edukasi terkait aktivitas fisik untuk pencegahan kelebihan berat badan pada dewasa muda di Pejagalan Jakarta Barat. Kegiatan pengabdian masyarakat dilakukan pada hari Kamis, tanggal 10 Mei 2023 pukul 13.00-16.00 di Pejagalan Jakarta Barat. Target sasaran kegiatan dewasa muda berusia 20-65 tahun. Status gizi dihitung berdasarkan rasio antara berat badan (BB) dalam satuan kg dan kuadrat dari tinggi badan (TB) dalam satuan meter. Peserta diberikan kuesioner terkait aktivitas fisik aktivitas fisik waktu luang godin shepard untuk mengetahui gambaran tingkat aktivitas fisik peserta Kegiatan pengabdian dilanjutkan penyuluhan kesehatan“Cegah Obesitas. Kegiatan diikuti 30 peserta dengan rentang usia 20-60 tahun, terdiri 16 peserta laki-laki dan 14 peserta perempuan. Berat badan peserta berkisar 47-93 kg dan tinggi badan 148-183 cm. Tingkat aktivitas fisik peserta penyuluhan adalah 20 peserta denga tingkat aktivitas fisik kurang dan 5 peserta denagn tingkat aktivitas tinggi. Peserta yang jarang berolahraga dalam 1 minggu sebanyak 20 (66,7%) dan 10 (33,3%) peserta rutin berolahraga. Peserta yang status gizi obesitas sebanyak 10 (33,3%) peserta dan 6 (20%) peserta termasuk status gizi berat badan lebih.